Nilai Karakter Islami Serial Kartun Boruto: Naruto Next Generation Episode 221−226 - Siti Suudiatul Mabruroh; Shidiq Ardianta (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
Film is a form of media that has great power in influencing, inspiring, and reflecting values ​​in society. Therefore, it is important to understand the values ​​contained in films, one of the films that has a lot of character values ​​is the cartoon series Boruto: Naruto Next Generations. The purpose of this study is to analyze and describe the character values ​​of honesty, hard work, and social care in the cartoon series Boruto: Naruto Next Generation episodes 221-226. This study used a qualitative approach, with literature study as a type, and data collection techniques in the form of documentation, using semiotic data analysis with Charles Sanders Peirce's semiotic analysis model, for data validity techniques using observation persistence. This research draws the conclusion that in the cartoon series Boruto: Naruto Next Generations episode 221−226, there are honest character values, namely acting according to the rules (not cheating) and telling the truth (not lying). The character values ​​of hard work include not giving up easily, making the best use of time, 3) Social caring character values, which include being attentive to others, helping people who are in misfortune.